2020
DOI: 10.3390/cells9102198
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Medium from Cells Overexpressing TDP-43 Alters the Metabolome of Recipient Cells

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease caused by the progressive death of both upper and lower motor neurons. The disease presents a poor prognosis, and patients usually die 2–5 years after the onset of symptoms. The hallmark of this disease is the presence of phosphorylated and ubiquitinated aggregates containing trans-active response DNA-binding protein-43 (TDP-43) in the cytoplasm of motor neurons. TDP-43 pathology has been associated with multiple pathways in ALS, such as metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…A number of prior studies have failed to identify any metabolic signature associated with the overexpression of a protein in a cell line. 42,43 A tree diagram (Figure 1F) derived from the score plot (Figure 1E DNAJA1 expression, indicating metabolome perturbations accumulated over time. However, the tree diagram indicates that the metabolome of WT-Bx cells did not change over time.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of prior studies have failed to identify any metabolic signature associated with the overexpression of a protein in a cell line. 42,43 A tree diagram (Figure 1F) derived from the score plot (Figure 1E DNAJA1 expression, indicating metabolome perturbations accumulated over time. However, the tree diagram indicates that the metabolome of WT-Bx cells did not change over time.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Importantly, these metabolic differences are likely due to the cellular activity of DNAJA1 instead of a generic response to the process of overexpressing a protein. A number of prior studies have failed to identify any metabolic signature associated with the overexpression of a protein in a cell line. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note however, that not all cell studies support the notion of TDP-43 propagation. Two reports have shown that while cells may release TDP-43 into the media, there is no evidence of uptake of this protein into recipient cells treated with the conditioned media [136,137]. The conditioned media did result in cytotoxicity and metabolic changes [137], suggesting that TDP-43 may have extracellular impacts.…”
Section: Tdp-43 Cell-to-cell Propagationmentioning
confidence: 96%
“…Two reports have shown that while cells may release TDP-43 into the media, there is no evidence of uptake of this protein into recipient cells treated with the conditioned media [136,137]. The conditioned media did result in cytotoxicity and metabolic changes [137], suggesting that TDP-43 may have extracellular impacts. Clearly, more work is required to fully understand the mechanism of spread of TDP-43 pathology, as well as identifying potential inter-versus extracellular effects.…”
Section: Tdp-43 Cell-to-cell Propagationmentioning
confidence: 96%